(untitled) (Research, Society and Development, 2021)
The phenomenon of the judicialization of health has increased the number of demands brought to the attention of judicial bodies throughout Brazil. In the municipality of Mossoró/ RN, the population seeks the Judiciary to see their right to perform surgical procedures of all kinds guaranteed, as is the case, for example, of elective surgeries. This study aimed to understand the factors that lead to judicialization, even in cases where the surgical procedure is offered through the Unified Health System (SUS). It is a qualitative and quantitative research, based on the study carried out in 45 court proceedings pending in the Courts of Fazenda Pública de Mossoró/RN, in addition to interviews with active professionals. The research verified the occurrence of mismanagement of public money when, being able to apply economical alternatives, the municipal public entity allows the judges to block public money for fund procedures without cheapening services. The detailed study of forty-five court proceedings, through qualitative and quantitative research, revealed judicialization for services already provided, in addition to procedures not covered by public health policies, unrestrained concession and the absence of a standard in the procedure adopted among judges in court proceedings.